2019
DOI: 10.1021/jacs.9b07286
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Complex Mediated Nitric Oxide Reductive Coupling: Ligand Hydrogen Bonding Derived Proton Transfer Promotes N2O(g) Release

Abstract: A cuprous chelate bearing a secondary sphere hydrogen bonding functionality, [(PV-tmpa)­CuI]+, transforms •NO(g) to N2O(g) in high-yields in methanol. Ligand derived proton transfer facilitates N–O bond cleavage of a putative hyponitrite intermediate releasing N2O(g), underscoring the crucial balance between H-bonding capabilities and acidities in (bio)­chemical •NO(g) coupling systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 77 publications
1
23
0
Order By: Relevance
“…Mutation of a Tyr to a Phe residue in the active site of FDPnor resulted in the loss of catalytic activity, and DFT calculations implicated the Tyr as providing a key hydrogen bond to an N−N coupled hyponitrite (ONNO 2− ) intermediate during NO reduction [27c, 33] . Hydrogen bonding between the solvent and NO‐derived intermediates has also been implicated as an important factor in other synthetic complexes [7g,n] …”
Section: Resultsmentioning
confidence: 99%
“…Mutation of a Tyr to a Phe residue in the active site of FDPnor resulted in the loss of catalytic activity, and DFT calculations implicated the Tyr as providing a key hydrogen bond to an N−N coupled hyponitrite (ONNO 2− ) intermediate during NO reduction [27c, 33] . Hydrogen bonding between the solvent and NO‐derived intermediates has also been implicated as an important factor in other synthetic complexes [7g,n] …”
Section: Resultsmentioning
confidence: 99%
“…In a follow-up study, Karlin and coworkers later reported a variation of this chemistry, where a TMPA derivative was used that carries hydrogen-bond donating amide groups in the SCS . Reaction of the corresponding Cu I complex [Cu­(PV-TMPA)] + (PV = pivolato) with NO was hypothesized to form a short-lived hyponitrite-bridged di-Cu II intermediate at low temperature, as determined by UV–vis spectroscopy.…”
Section: Non-heme Iron Centers and Nomentioning
confidence: 99%
“…Thus, hydrogen bonding likely plays an important role in facilitating NO disproportionation, much like with other examples of nearby Lewis acids and hydrogen bond donors aiding in transition metal complex reactivity with NO. [59][60][61] In particular, the hydrogen bond may help to further polarize the NO adduct, promoting its reaction with additional equivalents of nitric oxide to form a putative Co(N2O2) species. We postulate that the cobalt centers are then close enough across the pore…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%